2001
DOI: 10.1002/ppul.1109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fetal growth restriction on lung development before and after birth: A morphometric analysis

Abstract: Our aim was to determine the effects of fetal growth restriction (FGR) during late gestation on the structure of the lungs in the fetus near term and at 8 weeks after birth. The studies were performed using two groups of pregnant sheep and their offspring. In both groups, FGR was induced by umbilico-placental embolisation (UPE); for fetal studies, UPE was performed from 120 days of gestation until 140 days (term, approximately 146 days), when fetuses were killed for tissue analysis. For postnatal studies, UPE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
72
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 34 publications
20
72
1
Order By: Relevance
“…Despite increased cortisol concentrations, 1 wk of SUAL-induced IUGR alone did not alter fetal lung morphology. This is supported by a previous study in sheep in which umbilicoplacental embolization was used to induce IUGR (10). Following 20 d of umbilicoplacental embolization, tissue density and alveolar size and number were unaffected.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Despite increased cortisol concentrations, 1 wk of SUAL-induced IUGR alone did not alter fetal lung morphology. This is supported by a previous study in sheep in which umbilicoplacental embolization was used to induce IUGR (10). Following 20 d of umbilicoplacental embolization, tissue density and alveolar size and number were unaffected.…”
Section: Discussionsupporting
confidence: 81%
“…Following 20 d of umbilicoplacental embolization, tissue density and alveolar size and number were unaffected. However when these animals were studied postnatally, tissue density was increased at 8 wk of age whereas at 2 years of age the IUGR lung had fewer, larger alveoli (10,11). This suggests that while no structural changes are present in fetal tissue, experimental IUGR may induce morphological changes later in life.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, the degree of structural recovery may have been greater than that observed by comparing airways of 140-d-old fetuses and 8-wk-old animals. Although there were no differences between treatment groups in airway morphometry at 8 wk, our other studies in lambs subjected to IUGR have shown that persistent changes were present in aspects of lung function (13) and alveolar structure (12). It is possible that such alterations could account for some of the detrimental effects of IUGR on respiratory function reported in epidemiologic studies.…”
Section: Fetal Growth Restriction and Airway Developmentmentioning
confidence: 62%
“…Despite evidence that restriction of fetal growth impacts upon lung development (12,13), there have been few studies on the effects of growth restriction on airway development. One study examined the tracheal structure of fetal sheep after restriction of fetal growth induced by the restriction of placental growth (14).…”
mentioning
confidence: 99%